Preserving athletic performance at altitude with heat acclimation: A cross-adaptive approach - Albert, B.; Miller, M. G. (Strength and Conditioning Journal, 2024)
Decreased oxygen availability at high-altitudes, referred to as hypoxia, reduces physical capacity and places athletes at risk of illness. Accelerated warming in mountainous regions compounds the environmental burden of these settings. Cross-adaptation (CA) involves using 1 stressor (e.g., heat) to reduce the physiologic strain of another (e.g., altitude). CA has the potential to alleviate the adverse effects of unaccustomed environmental conditions on sports performance when other options are not feasible. Through repeated exposures, heat acclimation (HA) provides a valuable alternative for altitude preparation as global temperatures rise. Environmental stressors may occur alone or in combination, further supporting the use of HA to protect against life-threatening heat illness during simultaneous exposures. This review highlights the mechanisms of HA that support performance at altitude, synthesizes heat-hypoxia CA research, and provides practical recommendations for effective implementation.